The Factors Affecting Consumer Purchase Intention through Social Commerce – A Concept Paper - Norizan, Juliana; Mat Ali, Syukrina Alini; Ishak, Mohd Fikri (Information Management and Business Review, 2023)
Emerging economies are not excluded, where the emergence of e-commerce has now advanced towards a new branch of social commerce as a platform for business transactions as well as in attracting, creating, and maintaining customer relationships. E-commerce on social media platforms offers a practical means for businesses to connect with and sell to consumers. Major social networking sites have been actively developing their e-commerce features, allowing users to make purchases without leaving the site. Major social networking sites have been actively developing their e-commerce features, allowing users to make purchases without leaving the site. Social commerce has become popular due to its importance in e-commerce. The research in this area is still limited, especially on the factors that influence purchase intentions when using social commerce platforms. The purpose of this study is to examine the contribution and significance of affordance and trust theories among Malaysian users that underpin purchase intentions on social commerce platforms. This paper establishes a conceptual framework for consumers’ purchase intentions based on the SOR model. Social media platforms can be used by businesses to interact with customers and increase sales once they recognize their potential. PLS-SEM (Partial Least Squares Structural Equation Modeling) will be used to examine the data.